The Determinants of NPLs in Emerging Europe, 2000-2011 - Didar Erdinç; Eda Abazi (Journal of Economics and Political Economy, 2014)
The emerging Europe has been hardest hit by the surge in the non-performing loans (NPLs) in the aftermath of the global financial turbulence and the crisis-induced recession. The surge in the NPLs generated a severe banking distress, and left a legacy of a debt overhang that dramatically constrained bank lending and served as a drag on economic growth in the post-crisis period. We quantitatively study the determinants of loan losses in static and dynamic panel models with a focus on the linkages between the macro-financial vulnerabilities and a wide range of bank specific variables in 20 emerging European countries during 2000-2011. Our results indicate that the NPL dynamics have been particularly sensitive to real GDP growth, and inflation, while bank profitability as a proxy for management quality plays a significant role in constraining loan defaults. By contrast, higher lending rates may lead to adverse selection problems, and hence reduces loan quality. There is also some weak evidence that rapid credit growth as a measure of excessive risk taking in lending serves as a precursor to worsening loan portfolio quality. We observe, based on a unique data set, that banks in the region increasingly employ advanced risk management regimes (Internal Rating Based, IRB) with the potential to better monitor and evaluate loan quality and hence, rein on problem loans.
Keywords: G21; G28; G32; 330; Non-performing loans in emerging Europe; Panel estimation; Generalized Method of Moments